PEMIKIRAN EKONOMI ABU UBAID AL-BAGHDADI (Studi Kitab Al-Amwal) - & Jalaluddin, Asra Febriani (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-undangan, Ekonomi Islam, 2017)
Economic thought of Abu Ubaid reflects the significance of maintaining the society?s rights and obligations, making justice a central principle in running the government and building a sense of unity and shared responsibility. Abu Ubaid also explicitly states that the government is obliged to provide an adequate standard of living for every individual in a Muslim society. He said that state revenue (fai ', khumus, alms and zakat) have to be managed by the state and allocated to the community. In term of  monetary, he states that the money have to have intrinsict value, standard exchange rate and medium of exchange. He is of the opinion that only dinars and dirhams that deserve to be used as a medium of exchange because it has a stable value so the inflation flows which adversely affect the economy of the country can be avoided.